New systematic method to determine elastic constants and crack propagation thresholds of brittle rocks under triaxial compression - Yu, Hua (2022)
Elastic constants and crack propagation stress thresholds of brittle rocks are important mechanical properties for engineering applications. However, these properties are currently determined using methods with subjective interpreting procedures, which create cognitive biases leading to a higher degree of uncertainties. In this study, triaxial compression tests were conducted on Weber Sandstone collected from the Rock Springs Uplift, Wyoming. Nine rock specimens were treated in different geochemical conditions and tested for three different confining pressures at an in-situ pore pressure and temperature. A new method is proposed to systematically determine elastic constants and crack stress thresholds using linear and cubic regression functions to describe the linear and nonlinear stress–strain elastic behaviors, respectively. The statistical approach implemented in this new method eliminates bias due to the subjective interpretation of the nonlinear stress–strain data. The proposed method improves the consistency of elastic constant determinations by considering the linear elastic boundary of rocks and unambiguously determines the crack initiation threshold using the cubic regression function. Eliminating the subjectivity in data analysis, the new systematic method is beneficial for studying the nonlinear rock behavior and facilitating engineering applications.